Assessment of Vegetation Phenological Extractions Derived From Three Satellite-Derived Vegetation Indices Based on Different Extraction Algorithms Over the Tibetan Plateau - An, Chunchun; Dong, Zhi; Li, Hongli; Zhao, Wentai; Chen, Hailiang (Frontiers in Environmental Science, 2021)
Remote-sensing phenology retrieval can remedy the deficiencies in field investigations and has the advantage of catching the continuous characteristics of phenology on a large scale. However, there are some discrepancies in the results of remote-sensing phenology metrics derived from different vegetation indices based on different extraction algorithms, and there are few studies that evaluate the impact of different vegetation indices on phenology metrics extraction. In this study, three satellite-derived vegetation indices (EVI: Enhanced Vegetation Index, NDVI: Normalized Difference Vegetation Index, and Normalized Difference Phenology Index: NDPI, calculated using surface reflectance data from MOD09A1) and two algorithms were used to detect the start and end of growing season (SOS and EOS) in the Tibetan Plateau (TP). Then the retrieved SOS and EOS were evaluated from different aspects. Results showed that the missing rates of both SOS and EOS based on the STL trendline crossing method (STL) were higher than those based on the seasonal amplitude method (SA), and the missing rate varied using different vegetation indices among different vegetation types. And the temporal and spatial stability of phenology metrics based on SA using EVI or NDPI were more stable than those from others. The accuracy assessment based on ground observations showed that phenology metrics based on SA had better agreements with ground observations than those based on STL, and EVI or NDVI may be more appropriate for monitoring SOS than NDPI in TP, while EOS from NDPI had better agreements with ground-observed EOS. Besides, the phenology metrics over complex terrain also presented worse performances than those over flat terrain. Our findings suggest that previous results of inter-annual variability of phenology from a single data or method should be treated with caution.